Metal phthalocyanine-linked conjugated microporous polymer hybridized with carbon nanotubes as a high-performance flexible electrode for supercapacitors. (3rd September 2020) - Mei, Lan; Cui, Xu; Duan, Qian; Li, Yanhui; Lv, Xiaoling; Wang, Heng-guo
Abstract: Metal phthalocyanine-linked conjugated microporous polymers (MPc-CMPs) have huge potential applications in energy conversion and storage systems. However, the inherent low conductivity limits their practical application. Herein, the MPc-CMPs are hybridized with highly conductive carbon nanotubes (CNTs) via the easy vacuum filtration method. Interestingly, the composite (denoted as CoPc-CMP/CNTs) shows the flexible feature, which can be served as the flexible binder-free electrode for supercapacitors (SCs). As expected, the flexible CoPc-CMP/CNTs exhibits a high specific capacitance of 289.1 F g −1 at a current density of 1 A g −1 and good capacity retention of 82.4% over 1350 cycles at a high current density of 10 A g −1 . Furthermore, First-principle calculations are used to elucidate the superiority of CoPc-CMP to other analogues. The good electrochemical performance could be attributed to the synergistic effect from the high pseudocapacitance and good conductivity of CoPc-CMP as well as the capacitive contribution and good conductivity of CNTs. Our strategy provides a new avenue to develop the high-performance SCs via rational integration of MPc-CMPs with highly conductive CNTs. Graphical abstract: Metal phthalocyanine-linked conjugated microporous polymers are hybridized with highly conductive carbon nanotubes via the easy vacuum filtration method. Interestingly, the composite shows the flexible feature, which can be served as the flexible binder-free electrode for supercapacitors. Image 1 Highlights: Metal phthalocyanine-linked conjugated microporous polymers are synthesized. Polymers are hybridized with carbon nanotube to form a flexible electrode. The flexible electrode shows good electrochemical performance for supercapacitors. Density functional theory calculations reveal its metallic property and superiority.